The E27 β2-adrenergic Receptor Polymorphism Reduces the Risk of Myocardial Infarction in Dyslipidemic Young Males - Sala, Gianluca; Di Castelnuovo, Augusto; Cuomo, Laura; Gattone, Marinella; Giannuzzi, Pantaleo; Iacoviello, Licia; De Blasi, Antonio (Thrombosis and Haemostasis, 2001)
In the present study we evaluated whether two polymorphisms of β2-adrenergic receptors (β2-AR) gene (R16G and Q27E) could modify the risk of myocardial infarction (MI).Using a case-control design, we analyzed the data from 125 male patients who had experienced a first episode of MI before the age of 45 years and 108 male controls matched for age. The allele frequencies for R16G and Q27E were: G16=0.56 and E27=0.36 in patients with MI and G16=0.61 and E27=0.42 in the control group. There was a trend (not statistically significant) of decreasing MI risk according to E27 or G16 alleles. Combined effect between E27 allele and history of dyslipidemia has been observed. Whereas dyslipidemia conferred a relative risk of MI of 4.8 (P<0.001) compared with normolipidemia in the entire study population, the relative risk increased to 9.0 (P<0.001) in Q27 homozygotes with dyslipidemia, and decreased to 1.8 (P=0.36) in E27 homozygotes.Our results show that the E27 allele of the β2-adrenergic receptor has a significant protective effect on MI in dyslipidemic young male.
Keywords: β2-adrenergic receptor polymorphisms; myocardial infarction; dyslipidemia